Pelayanan e-KTP Dalam Mewujudkan Tertib Administrasi Kependudukan (Studi Pada Dinas Kependudukan dan Catatan Sipil Kota Malang) - aditya febrianto (Jurnal Administrasi Publik, 2014)
Abstract : e-KTP Service to Create Demographic Administration Order (Study at the Official of Demographic and Civil Registration in Malang City). Electronic Identity Card (e-KTP) is an effort taken by the government in regulating and managing demographic database that is then applicable to the other service sector. Malang City has high level of population growth and therefore, needs a system to manage its huge demographic database. The objectives of research are to describe the effort of the Official of Demographic and Civil Registration in Malang City in implementing e-KTP Program and to analyze the factors supporting and constraining this implementation. Research type is descriptive with qualitative approach. The description of e-KTP program service is focused on legal base, demographic data update, the issuance of demographic registration number, and data recording procedure, as well as factors supporting and constraining the implementation of this program. Result of research indicates that e-KTP program is a breakthrough of improving the service at demographic administration field.Keywords : service, demographic, e-KTPAbstraksi: Pelayanan e-KTP Dalam Mewujudkan Tertib Administrasi Kependudukan (Studi Pada Dinas Kependudukan dan Catatan Sipil Kota Malang). KTP elektronik merupakan upaya dari pemerintah di dalam mengatur serta mengelola database kependudukan yang kemudian dapat diterapkan pada bidang pelayanan yang lain. Kota Malang dengan tingkat pertumbuhan yang tinggi memerlukanÂ  sistem untuk mengelola database kependudukan. Tujuan penelitian ini adalah untuk menggambarkan upaya Dinas kependudukan dan Catatan Sipil Kota Malang dalam pelayanan program e-KTP dan menganalisis faktor pendukung dan penghambat. Jenis penelitian ini adalah deskriptif dengan pendekatan kualitatif. Gambaran pelayanan program e-KTP difokuskan pada dasar hukum, pemutakhiran data kependudukan, penerbitan nomor induk kependudukan,dan prosedur perekaman data, serta factor pendukung dan penghambat pelaksanaan program. Hasil penelitian menunjukkan bahwa program e-KTP merupakan terobosan di dalam upaya peningkatan pelayanan di bidang administrasi kependudukan.Katakunci: pelayanan, kependudukan, e-KTP Â Â